TRAIL AND SPIRITUALITY ON THE CORA CORALINA PATH: AN EXPERIENCE REPORT (Fiep Bulletin - online, 2026)
Long-distance walking has increasingly been recognized as a practice capable of integrating physical, emotional, social and spiritual dimensions of human experience. This study aimed to report and analyze a ten-day journey along the Caminho de Cora Coralina, in the state of Goiás, Brazil, seeking to understand how physical effort, contemplation of nature, social interactions and environmental immersion contribute to processes of inner renewal and integral spirituality. This experience report is based on a daily field diary and supported by a narrative literature review. The approximately 300-km route was completed between February 9 and 18, 2024, with systematic documentation of environmental conditions, emotional states, physical challenges and contemplative moments. The results indicate that the journey fostered states of presence, self-reflection and connection with the natural environment, while also strengthening social bonds and a sense of solidarity along the route. Elements such as prolonged physical effort, Cerrado landscapes, hospitality from local residents and moments of silence contributed to a form of spirituality integrated into the everyday rhythm of walking. The study concludes that the Caminho de Cora Coralina constitutes a formative and restorative environment with the potential to promote biopsychosocial well-being and integral spirituality through human movement in natural settings.
Keywords: Long-distance walking; Caminho de Cora; Spirituality; Nature; Trails